Structural and magnetic properties of BiFeO3-PbTiO3 polycrystals. (3rd October 2018) - Freitas, V. F.; Bonadio, T. G. M.; Thomen, D. M. N.; Miyahara, R. Y.; Silva, D. M.; Rosso, J. M.; Dias, G. S.; Cótica, L. F.; Santos, I. A.; Garcia, D.; Eiras, J. A.; Yokaichiya, F.; et al.
Abstract: In this manuscript, microstructural, structural and magnetic properties of pure and La doped (0.6)BiFeO3 -(0.4)PbTiO3 polycrystals were investigated. X-ray diffraction, transmission and scanning electron microscopy results reveal morphologically uniform particles of rhombohedral and rhombohedral/tetragonal symmetries for pure and La doped samples. An enhanced magnetization, characterized by slim loop hysteretic curves of null remnant magnetization and 2 emu/g saturation (15 kOe) magnetization, is observed at room temperature for samples with average particle size close to 5 nm.